Budaya Ekologis di Kalangan Generasi Z Melalui Tren Challenge Lingkungan di TikTok - Dzakirah Alzena Daiva (Jurnal Nomosleca, 2026)
This study examines the role of environmental challenge trends on TikTok in shaping ecological culture among Generation Z. The increasing prevalence of environmental anxiety and the shift of youth activism into digital spaces position TikTok as a strategic medium for fostering environmental awareness. This research adopts a qualitative approach using a literature review method grounded in an interpretive paradigm with purposive selection of relevant academic sources, analyzing academic sources related to ecological culture, Generation Z characteristics, and the role of social media in environmental issues. Data were analyzed through a descriptive-thematic approach to identify patterns of meaning, narratives, and digital practices associated with environmental challenge trends. The findings indicate that TikTok serves as a space for meaning construction, enabling Generation Z to express environmental concern through visual narratives, emotional engagement, and social interaction. Nevertheless, the ecological culture formed through digital participation remains ambivalent, as online engagement does not consistently translate into sustained collective action in offline contexts.